Obesity Related Glomerulopathy in Adolescent Women: The Effect of Body Surface Area. Issue 1 (27th January 2022) - Bielopolski, Dana; Singh, Neha; Bentur, Ohad S.; Renert-Yuval, Yael; MacArthur, Robert; Vasquez, Kimberly S.; Moftah, Dena S.; Vaughan, Roger D.; Charytan, David M.; Kost, Rhonda G.; Tobin, Jonathan N.
Key Points: Body surface area (BSA)–standardized eGFR creates similar rates of hyperfiltration across body mass index (BMI) groups. Creatinine clearance and absolute eGFR, adjusted to individual BSA, reflect BMI increase, unlike BSA-standardized eGFR. Absolute eGFR, adjusted to individual BSA, unmasks higher prevalence of hyperfiltration in patients who are obese, enabling timely intervention. Visual Abstract: Abstract : Background: Adolescent obesity, a risk factor for cardiorenal morbidity in adulthood, has reached epidemic proportions. Obesity-related glomerulopathy (ORG) has an early reversible stage of hyperfiltration. Age-appropriate formulae for eGFR, which are standardized to ideal body surface area (BSA) and provide assessment of kidney function in ml/min/1.73 m 2, may underestimate prevalence of early ORG. We investigated whether adjusting eGFR to actual BSA more readily identifies early ORG. Methods: We studied a cohort of 22, 417 young individuals, aged 12–21 years, from a New York metropolitan multi-institutional electronic health records clinical database. eGFR was calculated in two ways: BSA-standardized eGFR, and absolute eGFR. Hyperfiltration was defined above a threshold of 135 ml/min per 1.73 m 2 or 135 ml/min, respectively. The prevalence of hyperfiltration according to each formula was assessed in parallel to creatinine clearance. Results: Serum creatinine values and hyperfiltration prevalence according to BSA-standardized eGFR were similar, 13%–15%, across body mass index (BMI) groups. The prevalence of hyperfiltration determined by absolute eGFR differed across BMI groups: underweight, 2%; normal weight, 6%; overweight, 17%; and obese, 31%. This trend paralleled the rise in creatinine clearance across BMI groups. Conclusions: Absolute eGFR more readily identifies early ORG than the currently used formulae, which are adjusted to a standardized BSA and are not representative of current population BMI measures. Using absolute eGFR in clinical practice and research may improve the ability to identify, intervene, and reverse early ORG, which has great importance with increasing obesity rates.